2015
DOI: 10.5301/jva.5000390
|View full text |Cite
|
Sign up to set email alerts
|

The use of the early cannulation prosthetic graft (Acuseal) for angioaccess for haemodialysis

Abstract: These results show that, while providing patency results that compare favourably to those published for other types of regular prosthetic accesses, the conduits are amenable to very early cannulation with few cannulation-related complications. This leads to a dramatic reduction in the need for temporary or tunnelled catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 16 publications
(26 reference statements)
3
31
0
Order By: Relevance
“…Overall, our outcomes, particularly the 1-year secondary-patency rate of 58.3%, are congruent with those published in industry-sponsored trials as well as in the more stringent European setting. 7,8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, our outcomes, particularly the 1-year secondary-patency rate of 58.3%, are congruent with those published in industry-sponsored trials as well as in the more stringent European setting. 7,8…”
Section: Discussionmentioning
confidence: 99%
“…7,14,15 In Maytham’s independent European series of 55 Acuseal grafts, 1-year results were notable for 12 month primary patency of 46% and secondary patency of 61%, with 73% of patients being cannulated within 24 hr of graft placement. 8 The largest prospective series (138 grafts) was published by Glickman in 2015 and reported a primary patency and secondary patency at 12 months of 33% and 78%, respectively. 8 When comparing our findings to the independent European series, there is congruity; however, when compared to Glickman’s industry-supported trial’s 1-year results, the primary patency results are comparable, yet there was a significant disparity in the cumulative patency and the total number of reinterventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients who are predialysis, the urgency to initiate dialysis is a core consideration affecting AV access choice. For example, a CVC can be avoided by using a prosthetic early cannulation AV graft that can be used in as little as 24 hours after creation (1,2) in patients without an already established vascular access, who urgently need to initiate HD. In contrast, while AVFs should be considered in all appropriate patients, AVFs require a minimum of 4 weeks and up to 9 months before they are suitable for HD in North America.…”
Section: Demographicsmentioning
confidence: 99%
“…Instead, placement of an AVG that can be used within hours to days (for early cannulation grafts) to a couple of weeks (depending on the material used) has been r e v i e w AK Viecelli and CE Lok: Hemodialysis vascular access in the elderly shown to be cost saving and associated with similar survival, fewer interventions to enable HD, and shorter CVC dependence compared with an AVF. [37][38][39][40][41][42][43] In a recent randomized controlled trial comparing the use of early cannulation grafts as an alternative to tunnelled CVC (AEAVF), investigators found that use of early cannulation grafts was associated with reduced rates of culture-proven bacteremia and mortality (risk ratio for bacteremia at 6 months, 0.2; 95% confidence interval 0.12-0.56; P ¼ 0.02 and mortality risk ratio, 0.3; 95% confidence interval 0.08-0.45; P ¼ 0.04). 44 Although this study was performed in a population with an urgent need to begin dialysis, the use of early cannulation AVGs is a viable CVC-limiting strategy and may be particularly useful in patients with limited life expectancy and/or who are at high risk of fistula maturation failure (e.g., poor vessels).…”
Section: Suitability Of a Native Avf For The Elderly Patientmentioning
confidence: 99%